Electrically conductive polymers and composites for biomedical applications. Issue 47 (27th May 2015) - Kaur, Gagan; Adhikari, Raju; Cass, Peter; Bown, Mark; Gunatillake, Pathiraja
<x xml:space="preserve">Abstract</x> This paper provides a review of the recent advances made in the field of electroactive polymers and composites for biomedical applications.